Gestión de riesgo de desastres y capacidad de respuesta a las emergencias en el Centro de Salud de Moronacocha – Iquitos, 2022 - Salva Ahuite, Rose Mary (2023)
The objective of the study was to determine the relationship of disaster risk management with the response capacity of the personnel working at the Moronacocha Health Center, Iquitos 2022. Basic research, quantitative approach, non-experimental, cross-sectional, correlational design. It included a population of 127 workers to whom a questionnaire was applied. The study in its results determined that 60.6% of response capacity was medium and risk management 39.4% was medium. The study concluded: There is a statistical relationship between risk management and response capacity, as well as in its dimensions knowledge, resources and contingency of the personnel working in the Moronacocha Health Center.